2005
DOI: 10.1101/lm.89805
|View full text |Cite
|
Sign up to set email alerts
|

Working memory deficits in retinoid X receptor γ-deficient mice

Abstract: Retinoid signaling has been recently shown to be required for mnemonic functions in rodents. To dissect the behavioral and molecular mechanisms involved in this requirement, we have analyzed the spatial and recognition working memory in mice carrying null mutations of retinoid receptors RAR␤ and RXR␥. Double mutants appeared deficient in spatial working memory as tested in spontaneous alternation in the Y-maze and delayed nonmatch to place (DNMTP) test in the T-maze. These mutant mice did acquire, however, spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
85
0
6

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(95 citation statements)
references
References 77 publications
3
85
0
6
Order By: Relevance
“…Here we demonstrated that RAR␤/RXR␥, which were shown previously to be involved in STWM (Wietrzych et al, 2005), are required for LTDM and that, like RA treatment, nutritional vitamin A supplementation prevents the age-related decline in both STWM and LTDM performances, as well as in molecular markers of hippocampal function. The present findings support the hypothesis that hippocampal retinoid receptor signaling is critically implicated in cellular mechanisms sustaining STWM organization and LTDM formation.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Here we demonstrated that RAR␤/RXR␥, which were shown previously to be involved in STWM (Wietrzych et al, 2005), are required for LTDM and that, like RA treatment, nutritional vitamin A supplementation prevents the age-related decline in both STWM and LTDM performances, as well as in molecular markers of hippocampal function. The present findings support the hypothesis that hippocampal retinoid receptor signaling is critically implicated in cellular mechanisms sustaining STWM organization and LTDM formation.…”
Section: Introductionmentioning
confidence: 92%
“…Functional implication of retinoid signaling in hippocampal plasticity and spatial memory was demonstrated in rodents by knock-out of RAR␤ or RXR␤/␥ receptors (Chiang et al, 1998;Wietrzych et al, 2005), vitamin A deprivation (Misner et al, 2001;Cocco et al, 2002;Etchamendy et al, 2003b), and RA administration (Crandall et al, 2004). Furthermore, dysfunction of retinoid signaling pathway has been hypothesized to be involved in human neurodevelopmental pathologies such as schizophrenia or late-onset Alzheimer's disease (for review, Goodman, 1998Goodman, , 2006Goodman and Pardee, 2003;Palha and Goodman, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, antalarmin treatment normalized stress-increased same arm return ratio (treatment: F 1, 24 ¼ 8.757, p ¼ 0.007; interaction: F 1, 24 ¼ 4.663, p ¼ 0.041; Figure 5b), which reflects certain aspects of attention (Wall and Messier, 2002;Wietrzych et al, 2005). In each sample phase of the temporal order memory test, all groups of mice explored the two copies of an identical object similarly (Supplementary Figure S7d).…”
Section: Blockade Of Crf 1 Prevents Early-life Stress-induced Cognitimentioning
confidence: 99%
“…The total distance traveled, number of arm entries, spontaneous alternation ratio (Wang et al, 2013), and same arm return ratio (Wall and Messier, 2002;Wietrzych et al, 2005) were measured.…”
Section: Behavioral Testingmentioning
confidence: 99%